THE ROLE OF RUNNING IN STRENGTHENING THE RESPIRATORY AND CARDIOVASCULAR SYSTEMS - Dusuyarov Turaboy Bekmazarovich (Bright Mind Publishing, 2025)
This article analyzes the physiological changes that occur in the human respiratory and cardiovascular systems as a result of running exercises. Regular running scientifically highlights the importance of strengthening the respiratory heart muscles, increasing blood circulation efficiency, stabilizing blood pressure, and preventing heart diseases.
Keywords: Running, respiratory system, lung volume, respiratory rate, alveoli, oxygen exchange, respiratory muscles, pulmonary ventilation, diaphragmatic activity, respiratory adaptation, cardiovascular system, stroke volume, bradycardia, capillary, blood pressure.